1967
DOI: 10.1071/bi9670941
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Variation with Ophiobolus Graminis

Abstract: SummaryVariations were studied in the monosporous Fl progeny ot an isolate of Ophiobolus graminis from wheat. All Fl ascospores from perithecia on living host tissue were strongly pathogenic, but half from a perithecium in culture were weakly pathogenic. Perithecia were formed in culture and on host tissue only by strongly pathogenic progeny. Strongly pathogenic progeny survived well on artificially infected wheat straw buried in unsterilized soil, but weakly pathogenic progeny did not. Survival of all isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1968
1968
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Previously, Chambers and Flentje (1967b) studied the survival of strongly and weakly pathogenic monosporous isolates from a perithecium formed in culture; they found that strongly pathogenic isolates survived well on straw buried in unsterilized soil, but weakly pathogenic variants did not. It, therefore, seems probable that weakly pathogenic variants arise in nature, but are unable to survive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, Chambers and Flentje (1967b) studied the survival of strongly and weakly pathogenic monosporous isolates from a perithecium formed in culture; they found that strongly pathogenic isolates survived well on straw buried in unsterilized soil, but weakly pathogenic variants did not. It, therefore, seems probable that weakly pathogenic variants arise in nature, but are unable to survive.…”
Section: Discussionmentioning
confidence: 99%
“…(i) Isolates.-Details of the isolates used are given in Table 1. (ii) Method of Isolation.-Monosporous cultures were isolated by the technique of Chambers and Flentje (1967b). However, viable ascospores were obtained only from asci which discharged within 2 hr of being placed in water.…”
Section: Methodsmentioning
confidence: 99%
“…Garrett (1940Garrett ( , 1944 showed that amending the soil with inorganic nitrogen, or with nitrogen-rich organic matter, consistently prolonged survival in buried straw. This effect of nitrogen has been confirmed by Butler (1953Butler ( ,1959, Macer (1961) and Chambers & Flentje (1967). Garrett (1963Garrett ( , 1966Garrett ( , 1967 has recently discussed the mechanism of the effect, which results from the need for continued hyphal extension into fresh areas of substrate if maximum survival is to be achieved.…”
Section: Introductionmentioning
confidence: 74%
“…A calcareous sandy soil from Moonta, S.A. (Chambers and Flentje 1967b) was used for laboratory studies. Field experiments were carried out in a red-brown earth of the Urrbrae series at the Waite Agricultural Research Institute, S.A., and a grey silaceous sand of the Caitup series at Esperance Research Station, W.A.…”
Section: (B) Soilsmentioning
confidence: 99%